The Enhancement of a Saccharum spontaneum Population and a Genetic Impact Analysis of the Agronomic and Yield Traits of Its Progeny - Jiayong Liu; Maoyong Ran; Liping Zhao; Lianan Tao; Fenggang Zan; Li Yao; Xin Hu; Shenglin Ren; Yong Zhao; Hongming Xia; Jing Zhang; Xinyuan Pu; et al. (Plants, 2025)
Saccharum spontaneum serves as an essential genetic resource for sugarcane improvement. Traditional breeding methods, characterized by slow selection and limited germplasm exploitation, often lead to suboptimal progeny performance. In this study, we revised the utilization strategy by initially hybridizing several S. spontaneum clones, followed by intercrossing their F1 progeny to establish a heterogeneous ‘polymeric’ population, which was then subjected to ‘nobilization’. A natural Saccharum spontaneum (S0) plant was used as the parent to create a hybrid (S1) containing two S. spontaneum bloodlines. The agronomic traits of S1 were compared, leading to the identification of three superior hybrids. These hybrids were then crossed in a complete diallel design, resulting in six crosses. Significant genetic variation was observed for the agronomic traits. Compared with S0, the plant height in S1 increased by 31.5%, and by 32.22% in S2. The stem diameter in S1 increased by 38.71%, and by 51.61% in S2. The single stem weight increased by 125% in S1 and 150% in S2. Other yield traits also showed varying degrees of improvement. A correlation analysis indicated that the plant height, stalk diameter, single stalk weight, and leaf width were significantly positively correlated with yield, and the leaf width with brix. There was no significant correlation between the millable stalks and yield. This study successfully developed a novel S. spontaneum hybrid with significantly improved agronomic traits, enhancing the genetic foundation of S. spontaneum germplasm for nobilization breeding programs. These findings provide a valuable germplasm base for developing high-performance sugarcane varieties, improving the utilization of S. spontaneum.